Teachers’ emotional labor in parent–teacher interactions: key elements and theoretical logic from a grounded theory approach - Zhai, Li; Guo, Chen (Frontiers in Psychology, 2025)
In the context of home–school cooperation becoming an important part of global education reform, the burdens of teachers’ emotional labor in parent–teacher interactions has increased. Their emotional labor in parent–teacher interactions not only affects home–school cooperation but also influences teachers’ well-being both professionally and personally. In response to the challenge of growing emotional labor burdens on teachers, the research on the key elements and theoretical logic of teachers’ emotional labor in parent–teacher interactions is of great significance. Semi-structured interviews were held with 20 teachers in primary and secondary schools in China. Retrieved data were coded at three levels to explore the key elements of teachers’ emotional labor in parent–teacher interactions and construct a theoretical model of these elements. The model is structured around seven elements: emotional labor environment, personal characteristics, emotion competencies, emotional foundation, emotional interactions, emotional labor practices, and emotional labor consequences. The findings construct a theoretical framework for teachers’ emotional labor in parent–teacher interactions, enrich research on this topic from a relational dimension, and provide theoretical and practical insights.